In school and out of school digital use and the development of children's self‐regulation and social skills. (26th July 2021) - McNaughton, Stuart; Zhu, Tong; Rosedale, Naomi; Jesson, Rebecca; Oldehaver, Jacinta; Williamson, Rachel
Abstract : More needs to be known about the benefits and risks to the development of interpersonal and intrapersonal skills in ubiquitous digital environments at school and at home. Nine to 12‐year‐old students ( n  = 186) in a 1:1 digital programme serving low SES and culturally diverse communities rated their self‐regulation and social skills for both non‐digital and digital contexts. Downward trends in self‐regulation and related personality dimensions were found. Social skills were more variable. Students had heightened awareness of needing to self‐regulate in digital contexts, rating their self‐regulation lower than in non‐digital contexts. High frequencies and durations of fun activities at home (e.g., posting photos or blogs, chatting, and games) were associated with lower ratings. But fun activities were associated with higher ratings of social skills in digital contexts. High levels of parental monitoring were related to higher ratings of self‐regulation. These patterns reflect school‐wide norms and practices (students are socialized as digital citizens) as well as more general features of socialization at home. We conclude that self‐regulation and social skills are sensitive to contexts over the primary school years. Digital tools may be particularly 'impulsogenic', and students need context‐specific self‐regulatory strategies, but the tools create opportunities to develop valued social skills under specific conditions.